Mitigation strategies for ester bound 2-/3-MCPD and esterified glycidol in pre-fried breaded and frozen fish products. (15th April 2018) - Merkle, Sybille; Ostermeyer, Ute; Rohn, Sascha; Karl, Horst; Fritsche, Jan
Highlights: MCPD-E content of the oil and fish fingers increased during pre-frying over time. Major portions of MCPD-E and G-E in fish fingers were absorbed from the oil. Reduction of MCPD-E and G-E was achieved by addition of an adsorbent material. The removal of breading particles from the oil lead to reduction of MCPD-E. TPM and color analysis could be screening methods for estimating MCDP-E contents. Abstract: Pre-frying of chloride-containing raw materials (e.g., breaded frozen fish products) can lead to the formation of fatty acid esters of 2-monochloropropane-1, 3-diol, 3-monochloropropane-1, 2-diol (MCPD-E), and glycidol (G-E). The aim of the present study was to identify relevant parameters for the formation of these process contaminants during the pre-frying. Secondly, several mitigation approaches have been investigated. The major proportion of the MCPD-E and G-E in the fish products resulted from the pre-frying oil absorbed, while the temperature and the heating period of the pre-frying oil showed the strongest impact. A significant reduction of the MCPD-E content in the pre-frying oil was achieved by filtering-off solid breading particles. Additionally, the G-E content decreased resulting from the use of adsorbent materials. Moreover, the analyses of total polar material and the color intensity of the pre-frying oil are suggested as screening methods for estimating the MCPD-E and G-E contents in the fish products.